S1P-S1PR1 Signaling: the “Sphinx” in Osteoimmunology - Xiao, Lan; Zhou, Yinghong; Friis, Thor; Beagley, Kenneth; Xiao, Yin (Frontiers in Immunology, 2019)
The fundamental interaction between the immune and skeletal systems, termed as osteoimmunology, has been demonstrated to play indispensable roles in the maintenance of balance between bone resorption and formation. The pleiotropic sphingolipid metabolite, sphingosine 1-phosphate (S1P), together with its cognate receptor, sphingosine-1-phosphate receptor-1 (S1PR1), are known as key players in osteoimmunology due to the regulation on both immune system and bone remodeling. The role of S1P-S1PR1 signaling in bone remodeling can be directly targeting both osteoclastogenesis and osteogenesis. Meanwhile, inflammatory cell function and polarization in both adaptive immune (T cell subsets) and innate immune cells (macrophages) are also regulated by this signaling axis, suggesting that S1P-S1PR1 signaling could aslo indirectly regulate bone remodeling via modulating the immune system. Therefore, it could be likely that S1P-S1PR1 signaling might take part in the maintenance of continuous bone turnover under physiological conditions, while lead to the pathogenesis of bone deformities during inflammation. In this review, we summarized the immunological regulation of S1P-S1PR1 signal axis during bone remodeling with an emphasis on how osteo-immune regulators are affected by inflammation, an issue with relevance to chronical bone disorders such as rheumatoid arthritis, spondyloarthritis and periodontitis.